The emergence of Islamophobia in social networks - Hicham Zohir (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: There are now countless ways for people all over the world to connect and share information, thanks to the Internet’s expansion. Blogs and other forms of online social networking have made it possible for people from all walks of life to connect and have their voices heard without fear of retribution. Verifying the connection between social networks and the phenomenon of Islamophobia is crucial in light of the recent rise of Islamophobia in the West following several attacks committed by fanatical terrorists who have been attributed to Muslims. Methodology: To get to the bottom of things, we used a questionnaire to collect data and then analyzed it with content analysis. Findings: The study’s results corroborated the significance of social media in the emergence of Islamophobia. Implications/Novel Contribution: The efforts that were made to present a synthesis of works on Islamophobia, particularly those related to social networks, constituted an important step in this study and made it possible to highlight a certain number of studies that have dealt with the relationship between our two variables. This was an important step in the study because it highlighted a certain number of studies that dealt with the relationship between our two variables.